Degradation Kinetics of Vitamin C in Orange and Orange Juice during Storage - Zhang, Jialan; Han, Hongxia; Xia, Juan; Gao, Mengxiang (Advance Journal of Food Science and Technology, 2016)
The objective of this study was to determine Vitamin C (Vc) degradation in orange and orange juice during storage at different temperatures. Degradation kinetics of Vc in orange and orange juice was modeled by zero and first order reaction. Vc of orange and orange juices is on the thermal instability during storage, which was found to decrease significantly with increase in storage time and temperature. Compared with zero order, the degradation kinetics was better fitted to the first order reaction model for both orange and orange juice. Following the first order kinetic model, the reaction rate constant (k) of Vc increased from 0.0396 to 0.3573/d with the increase of temperature from 5 to 37°C for orange while the k ranged from 0.0460 to 0.2617/d for orange juice. The results indicated that the temperature had a great deal of influence on the degradation of Vc in orange and orange juice.